Factors Affecting Adoption of Nursing Process Approach - Dr. Abhijeet Shelke, Hemant Vitthal Thorat, Dr.Mahadeo B.Shinde (International Journal of Advanced Science and Technology, 2020)
Objective: (1)To assess the knowledge of student nurses regarding nursing process. (2)To assess clinical adoption of nursing process.(3)To assess the factors affecting adoption of nursing process.